SEMIGRUP – Γ YANG DIBANGKITKAN DARI SUATU SEMIGRUP - Sumanto, Y.D (MATEMATIKA, 2015)
Every Element on semigroup can be regarded as binary operation on . Furthermore every element semigroup can be defined a binary operation on , if is set of binary operation that is defined from element semigroup , then can be formed become semigroup .